Net land gain or loss for two Mississippi River diversions: Caernarvon and Davis Pond. Issue 6 (2nd September 2019) - Turner, R. Eugene; Layne, Michael; Mo, Yu; Swenson, Erick M.
Abstract : Coastal wetland restoration can be complex and expensive, so knowing long‐term consequences makes it important to inform decisions about if, when, and where to conduct restoration. We determined temporal changes in land gain and loss in receiving basins and adjacent reference areas for two diversions of the Mississippi River in south Louisiana (Davis Pond and Caernarvon initiated in 1991 and 2002, respectively). Water from both diversions went into receiving basins with vegetated areas as did the adjoining reference areas. The results from two different types of satellite imagery analyses demonstrate a net land loss after diversions began. The results were confirmed for the Caernarvon diversion using a before–after/control–impact analysis of independently collected data over a larger area of the estuary. These results are consistent with an analysis of land gain and loss after a natural levee break on the Mississippi River in 1973. The positive influences of adding new sediments were apparently counter‐balanced by other factors, and consistent with the conclusion from other studies indicating that increased nutrient supply and flooding are, by themselves, negative influences on marsh health. Modeling the ecosystem effects of diversions can be calibrated and tested using landscape‐scale analyses like this to understand the chronic and delayed effects, including the unintended consequences. Basing the legitimacy of river diversion on ecosystem modeling will be premature without successfully reproducing empirical results like these in ecosystem models.